Influence of occupation and education level on breast cancer stage at diagnosis, and treatment options in China: A nationwide, multicenter 10-year epidemiological study. Issue 15 (April 2017) - Liu, Yang; Zhang, Jian; Huang, Rong; Feng, Wei-Liang; Kong, Ya-Nan; Xu, Feng; Zhao, Lin; Song, Qing-Kun; Li, Jing; Zhang, Bao-Ning; Fan, Jin-Hu; Qiao, You-Lin; et al.
Abstract : Abstract: The objective of this study was to evaluate the impact of occupation and education level of Chinese female breast cancer patients on their cancer staging at diagnosis, clinical and pathological features, rate of implementation, and selection of treatment. The medical charts of 4211 confirmed female breast cancer cases diagnosed between 1999 and 2008, from 7 breast cancer centers spread across the whole of China, were reviewed. Data including information on the patient's sociodemographic status, clinical and pathological characteristics, implementation of clinical examination and treatment modalities were analyzed. In parallel, the associations between different occupations and level of educational attainment were analyzed in relation to tumor stage through TNM staging, clinical and pathological characteristics, implementation of clinical examination, and treatment patterns. Multivariate logistic regression was used to identify whether the occupation and education level of patients are independent factors of TNM staging at diagnosis. There were significant differences among different occupation groups and the education level of patients in regards to pathological characteristics and treatment choice. Both the occupation and education level of patients were independent factors of TNM staging at diagnosis. For patients within the lower-income occupation or lower educational attainment group, the tumor stage was later, the rates of implementation of relevant investigations were lower, as were the rates of radiotherapy, chemotherapy, and endocrine therapy. This study suggests that strategies should work toward developing more accurate and effective breast cancer prevention and treatment strategies aimed specifically at patients with lower educational attainment levels and at specific occupation groups.